Description of a new species of Victoriopisa Karaman & Barnard, 1979 (Crustacea: Amphipoda: Eriopisidae) from China, with a key to the genus Victoriopisa - Zhao, Shuangyan; Liu, Cunqi; Hou, Zhonge (Zootaxa, 2016)
Victoriopisa multiartus sp. nov. is described from mangrove in Qi’ao Island, China. The new species differs from the other nine species of the genus Victoriopisa in the gnathopod I sexual dimorphism; propodus palm of gnathopod II with two excavations in female and one excavation in male; and terminal article of outer ramus in uropod III expanded, oval-shaped. A key to the genus Victoriopisa with ten species and a map of their distribution are provided.